ENHANCING A MASTERY THE CONCEPT OF ELECTROLYTE SOLUTIONS AND NON ELECTROLYTE BY EMPIRICAL INDUCTIVE LEARNING CYCLE LEARNING MODELS - resi sari yandra; tasviri efkar; ila rosilawati (Universitas Lampung, 2012)
Abstract, chemistry learning in schools tends to just memorize the concepts and less able to use these concepts if faced problems in real life that associated with the concept held. The result is chemistry learning losing its appeal and its relevance to the real world that should be become the object of the science. Therefore, it is designed a learning through SBEI learning model.The Research aims to determine the effectiveness of the SBEI learning model in increasing mastery of concepts on electrolyte and non electrolyte solution material. This research using a quasi-experimental methods Non Equivalent (pretest and postest) Control Group Design. The research sample are X1 and X3 grade students of SMAN 1 Gadingrejo (State senior high school 1 Gadingrejo) 2011-2012 school year that have almost the same characteristics. This Effectiveness of SBEI learning model is measured based on significantly gain increase. The results showing that n-Gain average value of mastery on concepts for the control and experimental classes respectively are 0.498 and 0.572.Based on the hypothesis testing, improved that class with SBEI learning has higher mastery on concepts than conventional learning model. This shows that SBEI learning is more effective in mastering concept of electrolyte and non-electrolyte solutions.Keywords: learning by Empirical Inductive Learning Cycle models, concept mastery.